Chronic rhinosinusitis: is any indication for Caldwell-Luc approach in endoscopic sinus surgery era? - Lupoi, Daniel (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Caldwell-Luc procedure was the gold standard procedure for chronic maxillary sinusitis until the endoscopic sinus surgery developed more and more. The aim of this study was to show the importance of Caldwell-Luc surgical approach in endoscopic sinus surgery era. Methods: Prospective study between 2009 and 2019 in the ENT Department of the Clinical Hospital Sfânta Maria from Bucharest. The inclusion criteria were as follows: adult patients diagnosed clinical and paraclinical with isolated chronic maxillary rhinosinusitis in whom correctly conducted drug treatment failed and, according to current therapeutic guidelines, had indication for surgical treatment. The treatment method consisted of a surgical approach, which was classic or endoscopic, depending on the situation imposed on each patient. Results: The application of the inclusion criteria in the study led in a group of 521 patients, of which 282 men (54.12%) and 239 women (45.87%). Following the accounting of the days of hospitalization and those of medical leave at discharge, a number of days of absenteeism of 13.85 days resulted in the case of patients treated classically and 8.62 days for those treated endoscopically. Also the endoscopic group had a better endoscopic and VAS score postoperatively. Conclusions: Surgical treatment of maxillary sinus can be minimally invasive- endoscopic, extended endoscopic or classical open surgery. Open classic surgical treatment remains the last treatment alternative, with indication for rhinosinusal recurrences or the imminence of complications. Endoscopic surgery is the “gold standard” for chronic maxillary rhinosinusitis.